DIGITAL STORYTELLING AS AN INSTRUCTIONAL MEDIA TOOL WITHIN THE ELEMENTARY SCHOOL EDUCATION: A SYSTEMATIC REVIEW - M., F Kogila; Ibrahim Kadir, Abu Bakar (International Journal of Psychosocial Rehabilitation, 2020)
Although Digital Storytelling (DST) was definitely a popular educational media tool in training from the 1990s, there is a lack of evaluation of DST effectiveness in elementary schools’ training. For this reason, a systematic approach in reviewing existing literature has been used. Research articles were searched in electronic databases applying "digital storytelling" as a keyword and in the aspect of the "elementary school education." The systematic review listed 24 publications that meet the requirements above. Our analysis shows that the adoption of DST in the Asian and European countries has increased over the years. Upon content analysis, it was found that studies about DST in classrooms started in 2008, with the number of studies growing yearly and the highest number of studies conducted in Asian countries. The experiments had been mainly carried out in language guidance, accompanied by science learning. As a result, observational research is required to track the effect of DST studies and information on DST in the elementary school classroom. It’s extremely hoped the paper would find that DST is able to offer a strong learning experience covering a lot of what society expects will be noted and able to do within the 21st century.